Deformation and temperature behaviour during cold, warm and hot flat rolling of AA5454-O alloy - Sezek, S.; Aksakal, B. (Elsevier Sci Ltd, 2009)
AA5454-O aluminum alloy has been flat rolled as cold, warm and hot conditions for various temperature and deformation rates. The changes in microstructure and mechanical properties have been determined through tensile, hardness and microscopic analysis. Microscopic observations were made through optical and scanning electron microscopes and X-ray analysis was also conducted. The temperature and deformation rate had great influence on microstructure and fracture type of cold, warm and hot rolled alloy. The strain hardening exponent (n) decreased, and strain rate sensitivity exponent (m) increased with increasing process temperature and deformation rates. The hardness increased with increasing deformation rate and temperature, but reached to a maximum for 200 degrees C and 50% deformation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Forming; Non-ferrous metals; Plastic behaviour